Development of a patient-reported palliative care-specific health classification system: the POS-E - Murtagh, Fliss E. M.; Murtagh, Fliss E.M.; Dzingina, Mendwas; Higginson, Irene J.; McCrone, Paul; Murtagh, Fliss (The Patient - Patient-Centered Outcomes Research, 2017)
Background Generic preference-based measures are commonly used to estimate quality-adjusted life-years (QALYs) to inform resource-allocation decisions. However, concerns have been raised that generic measures may be inappropriate in palliative care. Objective Our objective was to derive a health-state classification system that is amenable to valuation from the ten-item Palliative Care Outcome Scale (POS), a widely used patient-reported outcome measure in palliative care. Methods The dimensional structure of the original POS was assessed using factor analysis. Item performance was assessed, using Rasch analysis and psychometric criteria, to enable the selection of items that represent the dimensions covered by the POS. Data from six studies of patients receiving palliative care were combined (N = 1011) and randomly split into two halves for development and validation. Analysis was undertaken on the development data, and results were validated by repeating the analysis with the validation dataset. Results Following Rasch and factor analyses, a classification system of seven items was derived. Each item had two to three levels. Rasch threshold map helped identify a set of 14 plausible health states that can be used for the valuation of the instrument to derive a preference-based index. Conclusion Combining factor analysis and Rasch analysis with psychometric criteria provides a valid method of constructing a classification system for a palliative care-specific preference-based measure. The next stage is to obtain preference weights so the measure can be used in economic evaluations in palliative care.
Keywords: Nursing (miscellaneous)